Analisis Faktor Resiko Mortalitas Covid 19 - Deli Mutiara Siregar; Eunice Kristia Sipayung (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Medical records are a source of data for hospitals that can be processed into statistics. Mortality statistics are included in health service statistics that are useful in efforts to maintain hospital quality. (Anggryani, 2021) Death or mortality is one of the three components of the demographic process that affect population structure. Thehigh mortality rate of the population in an area not only affects population growth, but is also a barometer of the high and low level of public health in the area. Mortality or death can happen to anyone, old, young, anytime and anywhere. Cases of death, especially in large numbers, are related to social, economic, customary, and environmental health problems. Death indicators are useful for monitoring the performance of central and local governments in improving community welfare. SARS-CoV-2 can affect anyone and cause different symptoms or severity, but individuals over the age of 60 with comorbidities such as diabetes, chronic respiratory disease, and cardiovascular disease are at higher risk of infection. The method in this article is Systematic review, where this article is done with a data set technique to review journals, literature searches, notes and reports related to articles. This systematic process of review is also used to collect data. Heart disease is significantly associated with an increased risk of death from COVID-19 patients.